2016
DOI: 10.1002/sono.12073
|View full text |Cite
|
Sign up to set email alerts
|

Stress and preterm birth: biological and vascular mechanisms affecting the feto‐placental circulation and the length of gestation

Abstract: Preterm birth is the leading cause of perinatal morbidity and mortality. Women experiencing high levels of stress in pregnancy are at an increased risk of preterm delivery. This review examines the biological pathways of the maternal stress response, in particular, the functioning of the maternal hypothalamic-pituitary-adrenal axis, and investigates the role of the placenta in altering this response mechanism. Furthermore, the impact of the products of hypothalamic-pituitary-adrenal axis on the blood flow resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…One possible explanation for this result is the saturation of maternal stress-induced response. Maternal stress may induce a response, such as hypothalamic-pituitary adrenal (HPA) axis dysfunction 32,33 or inflammatory immune response 34 which activates a mechanism leading to PTB and this response saturates and plateau once stress hits the level of depression.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this result is the saturation of maternal stress-induced response. Maternal stress may induce a response, such as hypothalamic-pituitary adrenal (HPA) axis dysfunction 32,33 or inflammatory immune response 34 which activates a mechanism leading to PTB and this response saturates and plateau once stress hits the level of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy-related stress is a predictor of preterm birth [ 1 ]. The resistance to placental blood flow mediated by the hypothalamic-pituitary-adrenal axis response to high-level maternal stress was proposed as the probable reason for the increase in preterm deliveries [ 16 ]. A statistically significant association between maternal anxiety, mental distress, psychiatric disorder, and Doppler velocimetry of umbilical and uterine arteries was not clearly established [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research about the association between maternal psychological stress and Doppler findings indicative of fetoplacental compromise, there exists a knowledge gap that prevents arriving at a definitive conclusion because of substantial methodological differences across studies [16]. The recent COVID-19 pandemic documented the occurrence of maternal psychological stress [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Although the mechanism of the association between prenatal stress and perinatal outcomes is still unknown, prenatal stress may be associated with the hypothalamicpituitary-adrenal axis and maternal-placental-fetal neuroendocrine system activity. 8,9 Cortisol could increase the placental corticotropinreleasing hormone concentration level, and a rise in this hormone level may contribute to the onset of labor, leading to preterm birth and low birth weight. 10,11 In addition, retrospective cohort studies reported that stress events reduce the secondary sex ratio, which is the ratio of male to female newborns at birth.…”
Section: Introductionmentioning
confidence: 99%
“…Severe stress, including natural disasters and life events, has been reported to adversely affect perinatal outcomes, such as preterm birth and low birth weight 5–7 . Although the mechanism of the association between prenatal stress and perinatal outcomes is still unknown, prenatal stress may be associated with the hypothalamic–pituitary–adrenal axis and maternal–placental–fetal neuroendocrine system activity 8,9 . Cortisol could increase the placental corticotropin‐releasing hormone concentration level, and a rise in this hormone level may contribute to the onset of labor, leading to preterm birth and low birth weight 10,11 .…”
Section: Introductionmentioning
confidence: 99%